Teologi Inklusif untuk Membangun Kerukunan (Analisis Teks Tutur Jatiswara) - I Komang Suastika Arimbawa; Putu Ayu Septiari Dewi (Sphatika: Jurnal Teologi, 2020)
Harmony can be interpreted as a living and living condition that reflects an atmosphere of peace, order, peace, prosperity, respect, respect, price respect, tolerance, mutual cooperation in accordance with religious teachings. Harmony that adheres to the teachings of each religion can make every group among fellow human beings who have different beliefs as an open group (inclusive). Regarding this reality, in the text of Tutur Jatiswara there is an inclusive theological concept that can be a "nutrient" to build harmony, so that a plural religious life can live harmoniously, peacefully and help one another in the joys and sorrows. Inclusive is a way of thinking and an open attitude to all differences. Inclusive theology opens the door to apology and recognizes the existence of truth and salvation in other religions. Based on several excerpts in the text of Tutur Jatiswara, that truth is not narrow and not exclusive, because the truth lies in a vast expanse. This means that the truth radiates on each side. Because it radiates on every side, humans must build an inclusive paradigm of thinking so that they can become 'religious people', not just 'feel' religious or do religious activities. By being a religious person, the application of life together will form mutual respect (price-respecting), compassion (love-loving), and fostering (respect) towards adherents of different religions because they have the same rights.